2007
DOI: 10.1158/0008-5472.can-06-4785
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a Member of the Inhibitor of Apoptosis Family, Is Induced by Photodynamic Therapy and Is a Target for Improving Treatment Response

Abstract: We observed that photodynamic therapy (PDT) induces the expression and phosphorylation of the inhibitor of apoptosis (IAP) protein survivin in murine and human cancer cells and tumors. Survivin inhibits caspase-9, blocks apoptosis, and is associated with resistance to chemotherapy and radiation. Survivin is a client protein for the 90-kDa heat shock protein (Hsp-90), and the binding of survivin to Hsp-90 assists in the maturation, proper folding, assembly, and transport of this IAP protein. A derivative of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 33 publications
(68 reference statements)
11
101
1
1
Order By: Relevance
“…We examined survivin, TS, and E-cadherin to ß-catenin/TCF4 signaling system in the current study, since those proteins play pivotal roles in colon carcinoma cells in terms of cell malignancy, differentiation, apoptosis, and responsiveness to FOLFIRI, the current regimen for colon cancer. Survivin is an anti-apoptotic protein that blocks apoptotic process in carcinoma cells, whereas resistance to apoptosis is a key mechanism for the cells to resist anticancer drugs (29)(30)(31). TS is a key enzyme involved in the de novo synthesis of DNA and is the molecular target of 5-FU (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We examined survivin, TS, and E-cadherin to ß-catenin/TCF4 signaling system in the current study, since those proteins play pivotal roles in colon carcinoma cells in terms of cell malignancy, differentiation, apoptosis, and responsiveness to FOLFIRI, the current regimen for colon cancer. Survivin is an anti-apoptotic protein that blocks apoptotic process in carcinoma cells, whereas resistance to apoptosis is a key mechanism for the cells to resist anticancer drugs (29)(30)(31). TS is a key enzyme involved in the de novo synthesis of DNA and is the molecular target of 5-FU (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these signals act as mediators or promoters of apoptosis, while some signals act as stress responses that promote the repair of or increase the resistance to PDT-induced damage (16). Effects of PDT may be determined by balancing death and survival for cancer therapy resistance mechanisms (17,18). In previous study, HSP70 was found to regulate the apoptosis of chemoresistant cells by inhibiting pro-apoptotic proteins (19,20).…”
Section: Introductionmentioning
confidence: 98%
“…Photodynamic therapy (PDT) and cytotoxic agents were found to enhance survivin (member of the inhibitor of apoptotic protein family) expression which desensitised these cells to apoptosis (Ferrario et al, 2007;Qiu et al, 2005). Other anti-apoptotic factors (e.g.…”
Section: Alternative Signalling Pathways/moleculesmentioning
confidence: 99%
“…Since Hsp90 interacts with several oncognenic proteins involved in melanoma, disrupting their interaction may reduce the stability of these pro-tumour proteins (Powers and Workman, 2006). In melanoma and breast cancer cells, survivin induced PDT resistance (Ferrario et al, 2007). PDT increased survivin expression and phosphorylation both in vitro (BA mouse breast cancer cells) and in vivo (C3H mice transplanted with BA cells).…”
Section: Heat Shock Protein 90mentioning
confidence: 99%
See 1 more Smart Citation